Resistance to Heterodera avenae in the rye genome of triticale - Asiedu, Robert; Fisher, J.M.; Driscoll, C.J. (1990)
The cereal cyst nematode,Heterodera avenue Wollenweber, is a serious pest of cereals in many countries. A high level of resistance to the unique Australian pathotype of the nematode has been demonstrated in a triticale line (T701-4-6), which was originally obtained from CIMMYT. The level of resistance is similar to that in rye cultivar, South Australian, but higher than that in the wheat line (AUS 10894), hitherto reported to have useful resistance to the Australian pathotype. The gene for resistance was located on rye chromosome 6 (6R) after backcrossing the T701-4-6 line to wheat and correlating the resistance with the presence of individual rye chromosomes identified by morphological, cytological, and isozyme markers. Preliminary evidence suggests that the gene is located on the long arm of 6R. To transfer the resistance to wheat, double monosomics of6R and6D in aph1bph1b homozygous background were selected from F2 progeny from a cross of disomic6R substitution for 6D to theph1bmutant. Selfed seeds from these F2 plants will be screened for wheat-rye chromosome recombinants.